Freedom of religion versus the right to a noise free environment (2017)
This paper addresses die tension between the rights to a noise free environment and the right to worship or freedom of religion. The paper adopts doctrinal and comparative analysis of legal research methodology. The paper undertakes review of pertinent Nigerian laws on noise pollution along with the constitutional provisions on freedom of religion. On a comparative basis, the paper examines the legal approaches of some other jurisdictions in the. drive to attain a noise free environment. The paper posits that the extant Nigerian legal regime for the control of religious noise pollution is inadequate; along that axis, the paper recommends some legal and pragmatic measures. Generally, the paper stresses the need for an appropriate balance between citizens' exercise of freedom to worship and the societal need for noise free environment.